The perception of the population of the city of Barreirinhas, Maranhão, about covid-19 (Research, Society and Development, 2020)
COVID-19 is the disease caused by the New Coronavirus (SARS-CoV-2), which has victimized thousands of people across the globe, mainly due to its high rate of infectiousness, becoming rapidly circulating worldwide, being considered as a World Pandemic. For this reason, the objective of this article was to know the perception of residents of the municipality of Barreirinhas, Maranhão, in relation to the disease mentioned above. This study is an exploratory research developed with quantitative and qualitative approaches, since obtaining the data, as well as in the analysis of the results, considering that, thus, it would be more positive to gain the core outlined by this research. The method used in this work was: i) the reading of literature and scientific / journalistic articles dealing with the New Coronavirus in Brazil and in the World; ii) elaboration of the virtual questionnaire; iii) sharing the online “form” link; iv) tabulation of data. The results show that the majority of the citizens of the city mentioned are aware of the danger of the pathology in focus, carrying out relevant actions to avoid contamination; however, the same residents show some dissatisfaction with the Federal and Municipal Governments, which, in the view of the residents, are still very inefficient in combating the epidemic. In the end, several actions were recommended to combat and improve the Public Health of the aforementioned Municipality in view of the pathology surveyed, as an example, the maintenance of the quarantine and more public investments in the above-mentioned area.